Is God a Woman? Female Faces of God in Contemporary Cinema - Irena Sever Globan (Religions)
Film, as a medium, serves not only as a significant source of entertainment but also as a powerful instrument in shaping attitudes, beliefs, behaviours, social norms, and identities. Since its inception, cinematic art has been closely intertwined with religious themes, with many film narratives drawing implicitly or explicitly from biblical texts and religious traditions. Consequently, theologians and ecclesiastical authorities were quick to identify film as a potential locus theologicus. Given film’s ability to spark debates on deeply ingrained views and beliefs, feminist theology, which critically reflects on gender power relations within religious communities and theological texts, finds it intriguing to explore how cinematic narratives can challenge the millennia-old depiction of God as a man. This article aims to examine how the art of cinema contributes to theological reflections on the female metaphors of God, particularly through female Christ-figures and God-figures, which occasionally appear in films such as Chocolat, All That Jazz, Always, Dogma, and The Shack. These characters defy traditional religious language, which often employs masculine imagery and metaphors for God, portraying female God as an independent chocolatier, a single mother, an elegant hairdresser, a beautiful young seductress, a curvaceous African American bread maker, and a witty, clownish girl. In these cinematic depictions, female God is compassionate, empathetic, kind, witty, forgiving, and profoundly in love with her human creations. At the same time, all of these female characters are powerful, assertive, strong, and self-confident.